Production Planning Improvement Stamping Plant Company (Case Study: PT.TDS) (The Indonesian Journal of Business Administration, 2013)
PT.TDS is a stamping plant company located in Bekasi, Indonesia. Their main costumers are automotives spare-parts and component suppliers.  In early 2012, PT.TDS experience loss due to the high number of cost of good sold (COGS) which cover 89% of revenue. It is estimated that the company will have a loss in the end of the year. Therefore, the company need to find alternatives to avoid and minimizes the estimated loss. Problem is cause by internal and external factors. This paper will focus on the internal factors that influence to the high of overtime wages which representing approximately 3 to 6 % cost of good sold monthly. Root cause of high overtime wages are includes poor productivity planning, increase absenteeism, and increase of reject rates.  A good production planning for PT.TDS should be able to lower overtime wages while at the same time anticipated increase of absenteeism and accommodate rework due to reject parts. Problem solution for PT.TDS are include improvement in production planning by using constant output strategy, controlling overtime through different working hour policy  based on job classification and new working scheduling system. By conduction recommended production planning improvement the company should be able to reduce COGS/sales from 89% to 84%. As the result, cost analysis of implementation shown that not only the company could avoid loss in future years but is also could generate profit. Proposed problem solution required participation from all departments related to production activities. To ensure related department received adequate knowledge regarding their roles in the new production system, development of proposed solution and training need to be conduct.  Keywords: Stamping plant, COGS reduction, Production planning